(untitled) (Mustansiria Dental Journal, 2018)
Abstract Background and objective: During root canal instrumentation irrigants, necrotic pulp tissue, microorganism and dentin debris may be extruded beyond the apex into the periradicular tissue. These extrusions may cause flare-up. The purpose of this study was to compare the amount of apically extruded debris with three rotary Nickel titanium instruments. Methods: Sixty single rooted, single canalled premolars were selected. The roots were divided randomly into three groups; (n = 10) according to the type of instrumentation system used, group 1“ProTaper Next” system, group 2 “One Shape” system and group 3 “Mani Silk” system. The Debris extruded during the instrumentation was collected and dried in preweighed vials and the amount of extruded debris was assessed with an electronic balance. Result: results showed that the Mani silk system extruded significantly less debris than the ProTaper Next and One shape systems (P < .05), and there is no significant difference in apically extruded debris between ProTaper Next group and One Shape group but the One Shape produced more debris than ProTaper Next. Conclusion: the Mani silk file instrument was behaved well during instrumentation and extruded less debris than the other groups.